2014
DOI: 10.1007/s12032-014-0273-4
|View full text |Cite
|
Sign up to set email alerts
|

X-linked inhibitor of apoptosis-associated factor l (XAFl) enhances the sensitivity of colorectal cancer cells to cisplatin

Abstract: The purpose of present study was to investigate the roles of X-linked inhibitor of apoptosis-associated factor l (XAFl) in regulation apoptosis of colorectal cancer (CRC) cells after treatment with cisplatin (DDP). A total of ten paired cancerous and non-cancerous tissues were collected from patients with CRC after surgery. The levels of XAFl protein were detected by Western blot. Primary CRC cells were separated from cancer tissues, and its viability or apoptosis after treatment with DDP was determined with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In hepatocellular carcinomas, the increased expression of XAF1 leads to an inhibition of tumor angiogenesis [64,67,68]. In ovarian carcinoma and colorectal cancer cells, the overexpression of XAF1 leads to a sensitization of the cells for cisplatin [69,70]. This fits to the observation that a reduced XAF1 expression leads to increased cisplatin resistance.…”
Section: Discussionsupporting
confidence: 67%
“…In hepatocellular carcinomas, the increased expression of XAF1 leads to an inhibition of tumor angiogenesis [64,67,68]. In ovarian carcinoma and colorectal cancer cells, the overexpression of XAF1 leads to a sensitization of the cells for cisplatin [69,70]. This fits to the observation that a reduced XAF1 expression leads to increased cisplatin resistance.…”
Section: Discussionsupporting
confidence: 67%
“…XIAP-associated factor 1 (XAF1) was identified as a XIAP-binding protein and could directly bind preferentially to XIAP and antagonize the anti-caspase activity of XIAP to induce apoptosis (26). Pro-apoptotic gene XAF1 was constantly expressed in normal and fetal tissues but weakly expressed in most human cancer cell lines and human cancer tissues such as ovarian, hepatocellular, colon, pancreatic cancer and melanoma (27)(28)(29)(30)(31). Recent studies had shown that XAF1 expression was relatively low in hepatocellular carcinoma cell lines and hepatoma tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a pro-apoptotic Smac3 splice variant of Smac/Diablo was found to accelerate XIAP autoubiquitination and destruction and enhanced apoptotic cell death in HeLa cells exposed to multiple chemotherapeutics [ 80 ]. XAF1 is a pro-apoptotic protein that also targets XIAP and can enhance tumor cell susceptibility to cisplatin [ 81 ] and radiotherapy [ 82 ]. While XAF1 expression in tumor cells is generally very low, quantities of alternatively spliced truncated isoforms lacking the XIAP interaction have been found to increase in some aggressive cancers and have been suggested as potential biomarkers of disease status [ 83 , 84 ].…”
Section: Other Apoptotic Regulatorsmentioning
confidence: 99%